MODEL TERINTEGRASI KEPUASAN PASIEN PADA RUMAH SAKIT GIGI DAN MULUT PENDIDIKAN (RSGMP) DI JAKARTA - Putri Handara (Jurnal Manajemen dan Pemasaran Jasa, 2014)
The background of this research was every service provider, including RSGMP are expecting to maintain customer / customer loyalty in long period of time. Loyalty is directly influenced by the satisfaction / dissatisfaction of patients that have been accumulated within a certain of period. If the performance fulfills the expectations, customer would satisfy, otherwise, if the performance was below expectations, the consumer is not satisfied. Outcome quality, Interaction quality andPeer-to-peer quality are the dimensions of Service quality. Service quality has an impact on Customer satisfaction, thus need to be considered by the dentist to create Customer satisfaction.The Objectives of this research was to propose and test a theoretical model of the relationship among service quality, customer satisfaction, and customer loyalty. Other than that to testing the role of customer satisfaction as mediator in the relationship between Outcome quality, quality Interaction and Peer-to-peer quality with Customer loyaltyThe design of this study using hypothesis testing aims to examine the relationship between the variables. Samples of 150 patients were selected based on the patient of RSGMP in Jakarta, whichhas been treated at least 1 year in the same place. The sampling technique used was purposive sampling. The model used is based on the research criteria. Data analysis used in this research was using the primary data. Data were collected by questionnaire technique that is by providing a written statement to the respondents. Furthermore, the respondents respond to the statement given. Questionnaires were administered are closed and in which the answer is already provided.The result of this research concludes that outcome quality, interaction quality, and peer-to-peer quality have significantly influence customer satisfaction, and in turn impacted the customer loyalty. This research shows that outcome quality, interaction quality, and peer-to-peer quality should be considered as pivotal elements in creating customer satisfaction and that customer satisfaction should be treated as strategic variable to enhance customer loyalty.Keywords: Outcome quality, Interaction quality and Peer-to-peer quality, Service quality, Customer satisfaction, Customer Loyalty